“The Cartography of the Unseen” - Bigon, Liora; Njoh, Ambe (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
An international exhibition presented at HIT’s Research Gallery, Master’s Program in Integrated Design, Faculty of Design, Israel, February 2015; Curator: Dr. Yael Eylat Van-Essen; Co-researcher and assistant curator: Dr. Sayfan Borghini; Academic director: Dr. Dror K. Levi.